The skeletal amino acid composition of the marine demosponge Aplysina cavernicola - Ueberlein, Susanne; Machill, Susanne; Niemann, Hendrik; Proksch, Peter; Brunner, Eike (Marine Drugs, 2014)
It has been discovered during the past few years that demosponges of the order Verongida such as Aplysina cavernicola exhibit chitin-based skeletons. Verongida sponges are well known to produce bioactive brominated tyrosine derivatives. We could recently demonstrate that brominated compounds do not exclusively occur in the cellular matrix but also in the skeletons of the marine sponges Aplysina cavernicola and Ianthella basta. Our measurements imply that these yet unknown compounds are strongly, possibly covalently bound to the sponge skeletons. In the present work, we determined the skeletal amino acid composition of the demosponge A. cavernicola especially with respect to the presence of halogenated amino acids. The investigations of the skeletons before and after MeOH extraction confirmed that only a small amount of the brominated skeleton-bound compounds dissolves in MeOH. The main part of the brominated compounds is strongly attached to the skeletons but can be extracted for example by using Ba(OH)2. Various halogenated tyrosine derivatives were identified by GC-MS and LC-MS in these Ba(OH)2 extracts of the skeletons.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Amino acid composition; Demosponges; GC-MS; Halogenated amino acids; LC-MS; Skeletons